Multiple functions of Na/K-ATPase in dopamine-induced salivation of the Blacklegged tick, Ixodes scapularis - Kim, Donghun; Urban, Joshua; Boyle, Daniel L.; Park, Yoonseong (My University, 2016)
Control of salivary secretion in ticks involves autocrine dopamine activating two dopamine receptors: D1 and Invertebrate-specific D1-like dopamine receptors. In this study, we investigated Na/K-ATPase as an important component of the secretory process. Immunoreactivity for Na/K-ATPase revealed basal infolding of lamellate cells in type-I, abluminal interstitial (epithelial) cells in type-II, and labyrinth-like infolding structures opening towards the lumen in type-III acini. Ouabain (10 mu mol l(-1)), a specific inhibitor of Na/K-ATPase, abolished dopamine-induced salivary secretion by suppressing fluid transport in type III acini. At 1 mu mol l(-1), ouabain, the secreted saliva was hyperosmotic. This suggests that ouabain also inhibits an ion resorptive function of Na/K-ATPase in the type I acini. Dopamine/ouabain were not involved in activation of protein secretion, while dopamine-induced saliva contained constitutively basal level of protein. We hypothesize that the dopamine-dependent primary saliva formation, mediated by Na/K-ATPase in type III and type II acini, is followed by a dopamine-independent resorptive function of Na/K-ATPase in type I acini located in the proximal end of the salivary duct.
Citation: Kim, D., Urban, J., Boyle, D. L., & Park, Y. (2016). Multiple functions of Na/K-ATPase in dopamine-induced salivation of the Blacklegged tick, Ixodes scapularis. Scientific Reports, 6, 13. doi:10.1038/srep21047
Keywords: Lone Star Tick; Amblyomma-Americanum L; Vector R-Appendiculatus; East; Coast Fever; Fluid Secretion